The Effectiveness of the Internship Program for Vocational High School Students Using the CIPP Method - Ali Yusuf, Furtasan; Basrowi (JTP - Jurnal Teknologi Pendidikan, 2023)
The internship program is an important program in educational institutions, especially Vocational High Schools (SMK) in Indonesia. The purpose of this study was to evaluate the success rate of the Program in honing students' skills and preparing students for the world of work. This research is an evaluation approach with the CIPP model or context, input, process, and product. The study was conducted on 100 SMK students who had completed the internship program during the Covid-19 pandemic. The results showed that the implementation of the internship program from context, input, process, to product showed a good category, so this program was still feasible to continue. In the future, the Head of Vocational School can motivate students regarding all elements of the internship program, so that the quality of this program is in line with the goals of National Education in improving the quality of reliable and ready-to-use human resources. .